Advanced ages at death in Sápmi during the eighteenth and nineteenth centuries: With special attention to longevity among the Sami population. Issue 1 (2nd January 2016) - Karlsson, Lena
Abstract: This article examines advanced ages at death in a historical population in northern Sweden between 1780 and 1900. The source material used is a set of data files from the Demographic Data Base at Umeå University supplemented with the search tool Indiko. The belief that the Sami died at very old ages was tested, and life tables and values of remaining life expectancies at older ages were calculated. The information of the age at death was analysed using a model containing four levels of certainty. The analysis reveals that the Sami did not live to extreme ages. The analysis also reveals large differences between the parishes concerning extreme longevity and correctness of age at death.